Optimal Design of PSS on SMIB Using Particle Swarm Optimization - Djalal, Muhammad Ruswandi; Saini, Makmur; Yunus, A.M Shiddiq (Politeknik Negeri Ujung Pandang, 2021)
Dynamic disturbances in the power system are caused by sudden changes in load. This condition causes the stability of the generator to be disturbed, such as the emergence of oscillations in the generator in the form of oscillations of frequency and rotor angle. Power System Stabilizer (PSS) is an additional control that can increase generator stability. To get optimal PSS performance, proper tuning of PSS parameters is needed. Optimal performance of PSS can cause the frequency response and angle of the SMIB rotor to be stable. In this study, PSO is used for optimization of PSS parameters. PSS is able to provide stability so that overshoot oscillations can be suppressed, as well as faster settling time performance for the system to reach steady state conditions. To test the reliability of the SMIB, a case study of adding and subtracting loads was used.